Regenerasi Jeruk Siam melalui Embriogenesis Somatik - Ali Husni; Agus Purwito; Ika Mariska; Sudarsono Sudarsono (Jurnal AgroBiogen, 2010)
The Regenerated of Siam Tangerin through SomaticEmbryogenesis. Ali Husni, Agus Purwito, Ika Mariska,and Sudarsono. Somatic embryogenesis occurs in mostplants that are cultured on a suitable medium in vitro.Somatic embryo may arise from single cells and the embryogeniccells are widely applicable in plant propagation,genetic manipulation and transgenic technologies. Thepresent study was carried out to develop an effectivesomatic embryogenesis technique to regenerate Siamtangerine plants. Materials used in this study were nucellartissues of young fruits (30-90 days post anthesis). Inductionof embryogenic calli was done by culturing the tissues onthree different basal media (MS, MW and MT). Embryomaturation was done on the MW medium + ABA (0; 0.1; 0.3;dan 0.5 mg/l), while germination to plantlet developmentwas done on WS medium + GA3 (0, 0.1, 0.3, and 0.5 mg/l).The results showed that among the three media, MW wasthe best medium for callus induction from nucellar tissueswith a success rates 98% for Simadu and 100% forPontianak. The best maturation of embryo somatic wasdone on MW medium + ABA 0.5 mg/l with success rates99%, while the best medium for germination and developmentinto planlets was MW medium + 0.5 mg/l GA3 with asuccess rate 58%.